Analisis Pengembangan Produk Berbasis Quality Function Deployment (Qfd) (Studi Kasus pada Produk Susu PT MSA) - Okky Rizkia Yustian (Jurnal Ekonomi dan Bisnis, 2015)
Product developments are motivated by science and technology, change ofconsumer’s demands, competition, and requirement to improve profit. This research is intended to figure out and analyze the tools applied in the PT MSA’s product development and its alternatives. Quality Function Deployment (QFD) is used to determine product attributes for consumer’s demand, company’s performance, level of interest, technical parameters, requirement of process, and quality procedures to improve the products. This research is designed as a quantitative research method. QFD application in PT MSA results 15 product attributes, which are demanded by consumers. Those attributes are interpreted through 9 technical parameters in House of Quality (HOQ) for packaged fresh milk, and 15 product attributes for yoghurt. Based on the priority analysis, PT MSA will conduct their business decision to develop yoghurt product, which is expected to increase the total sales.